Thermo-Hygral Analysis on Long-Term Natural Frequency of RC Buildings with Different Dimensions - Chijiwa, Nobuhiro; Maekawa, Koichi; Kurihara, Ryota (Journal of Advanced Concrete Technology, 2017)
Gradual decay of natural frequency of reinforced concrete (RC) buildings is computationally investigated in view of the long-term moisture loss and associated shrinkage of concrete. The thermo-hygral analysis for RC lifetime over sev-eral decades is applied with monitoring data of existing multi-story buildings and nuclear power plants in service. The reduced natural frequency is numerically reproduced with delayed cracking near junction planes between structural members of different dimensions in multi-story buildings and dispersed cracks close to the surfaces of RC thick walls of nuclear power plants. In order to quantitatively clarify the impact of drying shrinkage, both sealed and open boundary conditions for moisture migration are assumed at simulation. It is also confirmed logically that the rate of decay for the natural frequency of the middle story RC building is faster because of the small thickness of walls, slabs and columns compared to structural members of nuclear power plants.